Influence of information technology, skills and knowledge, and financial resources on inventory management practices among small and medium retailers in Malaysia / Tuan Zainun Tuan Mat ...[et al.] - Tuan Mat, Tuan Zainun; Md Johari, Nor Raihan; Abdul Azis, Maz Ainy; Hashim, Mohd Ridzuan (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, Shah Alam, 2018)
Small-medium Enterprises (SMEs) play a vital role in the Malaysian economy. One of the rapidly growing SMEs in Malaysia is the retail industry. One important element in improving the growth of SME retailers is inventory management, as it assists the SME retailers in managing their inventories. SMEs face difficulties in securing financial resources, which inhibits the adoption of computerized inventory systems, as well as limited skill and knowledge in managing their inventory, are among the major problems that causes a less effective inventory management in retail SMEs. Thus, this study aims to investigate the impact of these three factors on inventory management practices of retail SMEs. 120 questionnaires were distributed to the SMEs in the retail industry, and 100 companies responded. Findings showed that the level of inventory management practices among retail SMEs is moderate. Skills and knowledge, and information technology influence inventory management practices of retail SMEs. However financial resources do not influence inventory management practices of retail SMEs in Malaysia suggesting that they do not have problems in getting financial resources as majority of them have received funds from the government.